Development of PjBL-based Electrostatics Module to Improve Students' Experimentation Ability - Asrar, Allan; Z, Zulpadrianto (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to develop PjBL (Project-based Learning) based teaching materials in the context of magnetic electricity learning and measure its impact on improving students' experimental abilities. The development method of these teaching materials follows the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The analysis stage includes the needs of teaching materials, student characteristics, and learning material analysis. The design of teaching materials involves creating flowcharts and interactive multimedia storyboards. Development involves realizing the product design in the form of e-modules and validating the product by experts. The implementation stage is carried out to test the learning outcomes using e-modules on students. Evaluation is conducted to assess the effectiveness of teaching materials based on the analysis results at the implementation stage. This research shows that PjBL-based teaching materials are effective in improving students' understanding of concepts and experimental skills. These findings provide a significant contribution to higher education development by strengthening project-based learning approaches to facilitate deeper understanding and practical skills in the field of magnetic electricity.